An experimental method for detecting objects in an aqueous environment - Kuzmin Yuri; Proshkin Stanislav (EPJ Web of Conferences)
This research introduces a novel experimental approach for identifying conductive and non-conductive objects submerged in shallow water using grounded cables. The methodology is underpinned by a comprehensive mathematical analysis of electromagnetic field diffraction caused by elongated conductive and non-conductive spheroids in an aqueous environment, specifically when interacting with a grounded cable. The experimental configuration employs a parallel arrangement of a generator and two receiving electrode antennas. A key feature of this technique is its ability to distinguish an object's unique flow characteristic from ambient noise. This is achieved through the application of digital hardware and software filtering to a modulated sinusoidal signal. To facilitate this process, the researchers developed a specialized algorithm designed to filter out pulse and fluctuation interference. This innovative approach represents a significant advancement in underwater object detection, offering potential applications in various fields such as marine archaeology, environmental monitoring, and underwater infrastructure inspection.